Isolasi dan Karakterisasi Bakteri Asal Sumber Air Panas Non-Vulkanik - Rahmad Lingga; Budi Afriyansyah; Reti Septiani; Ina Miranti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to isolate and characterize bacteria that live in hot springs on Bangka Island. The research methods used include bacterial isolation; morphological characterization, Gram group determination and biochemical tests; identification; and thermophilic bacteria temperature resistance test. Hot water samples were obtained from 2 locations, namely Pemali Village and Permis Village. The hot water temperature range at both locations is between 38ºC to 52ºC. The results showed that 22 pure isolates were consisting of 9 isolates from Permis Village and 13 isolates from Pemali Village. In conclusion, the characterization results showed that all bacterial isolates were gram-negative bacteria with various biochemical characteristics. Keywords: Thermophilic Bacteria, Non-Volcanic, Bangka Island